Race, Class and Income Inequality in Brazil: A Social Trajectory Analysis - André Salata (Universidade do Estado do Rio de Janeiro, 2020)
The article deals with the relationship between race, class and income in Brazil, with the main objective of investigating the determinants of racial inequality in the countrys labour market. By making use of structural equation models, it analyses the process of setting income differentials between whites and blacks, from their social origin to the definition of wages, through schooling and occupational allocation. The analysis, based on data from the Brazilian National Household Sample Survey, collected in 2014, allows us to compare direct, indirect and total effects of race and social origin on income from work. Results show that, although the total effects of social origin are larger than racial effects, the former cannot explain most disadvantages suffered by blacks nowadays in Brazil, which occur mainly indirectly through education and occupation. Thus, the study brings new, updated and more detailed evidence to a long-standing debate.